2021
DOI: 10.1177/03331024211033829
|View full text |Cite
|
Sign up to set email alerts
|

Measuring headache day severity using multiple features in daily diary designs

Abstract: Objective Though migraine is thought of as a symptom complex, symptoms are typically assessed one at a time. For use in clinical research, we developed a composite measure of headache day severity by combining eight well-known symptoms captured in daily diaries. Subjects and Methods Data came from adults with a self-reported diagnosis of migraine (n  =  4380) who provided daily diary information assessed using a novel digital platform. Nine observed features theoretically linked to headache day severity were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…As an alternative, one could explore trajectories of latent severity scores. McGinley et al used eight common migraine symptoms to create a latent severity score and demonstrated that it can predict productivity losses and health‐care resource use 40 . The LCM‐based approach did not incorporate the data on participant‐designated MBS in the model but included the presence/absence of each migraine‐associated symptom as input.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, one could explore trajectories of latent severity scores. McGinley et al used eight common migraine symptoms to create a latent severity score and demonstrated that it can predict productivity losses and health‐care resource use 40 . The LCM‐based approach did not incorporate the data on participant‐designated MBS in the model but included the presence/absence of each migraine‐associated symptom as input.…”
Section: Discussionmentioning
confidence: 99%